TARI REMO JOMBANGAN SEBAGAI TARI PENYAMBUTAN KEBUDAYAAN KHAS JOMBANG - Wardana, Veronica Michelle Aprilia (Greget : Jurnal Kreativitas dan Studi Tari, 2024)
Remo Dance is one of the cultural heritages that has been introduced since ancient times. This type of dance is often displayed during a welcome ceRemony in Jombang, East Java. Remo dance will often be found in several events, especially on Ludruk or the National Grand Day. To discuss this object, the authors use qualitative research methods by analyzing several books and by the method of Internet research. The author's analysis shows that historically Remo dance comes from the city of Jombang, but is often also used by surrounding communities such as Surabaya, Mojokerto, Malang, Nganjuk, etc. Based on historical records, Remo Dance was originally created in the village of Ceweng, Diwek District, Jombang. In the beginning, the dance was made by street artists in the past by giving the theme of a prince who is known to be valiant and brave. The first time this dance was introduced was by way of traveling the streets and busking. Furthermore, this dance was enabled in certain occasions, especially the Ludruk show. Along with the development of the dance concept, this type of dance is widely known by the wider community, especially neighboring areas. Furthermore, this dance is adapted to the traditions in the local area.